Laundry fragrance keeping beads and preparation method thereof
Patent Information
- Application Number
- CN202611081369.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-21
- Publication Date
- 2026-10-13
AI Technical Summary
现阶段商用留香珠水溶膜多采用单一淀粉或聚乙烯醇材料制备,该类成膜材料在实际应用中仍存在诸多缺陷:一方面传统成膜体系分子网络结构单一,膜体柔韧性差、抗拉强度低,在仓储、运输过程中受挤压、摩擦及温湿度波动影响,极易出现脆裂、破膜漏香等问题,严重影响留香珠结构稳定性;另一方面常规水溶膜不具备抗菌能力,留香珠长期储存于潮湿环境中,膜体表面易附着并滋生细菌、霉菌等微生物,造成产品发霉变质、产生异味,缩短产品货架期
[0016]本发明的有益效果:本申请以多糖类材料、吸附剂、季铵盐类材料、多元醇、油酸酰胺、氧化钙和改性淀粉作为水溶膜的制备原料,以改性淀粉与多糖类材料作为复合成膜基体,辅以吸附剂、季铵盐类材料、多元醇、油酸酰胺及氧化钙制备多功能水溶膜,各组分通过氢键缔合、物理填充、与复合抗菌等作用,构筑稳定的三维网状成膜结构,有效的提高了水溶膜的力学性能和抗菌性能,从而提高洗衣留香珠的稳定性和抗菌性能。
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] This invention relates to the field of detergent technology, specifically to a laundry fragrance bead and its preparation method. Background Technology
[0002] Fragrance beads, as a new type of laundry detergent additive, have been widely used in the laundry and care industry due to their excellent fragrance-enhancing and fragrance-retaining effects.
[0003] Currently, most fragrance beads on the market are made by encapsulating fragrance and functional additives in a water-soluble film. The structural strength, stability, and antibacterial properties of the water-soluble film directly determine the shelf life and quality of the fragrance beads. At present, commercially available fragrance bead water-soluble films are mostly made from single starch or polyvinyl alcohol materials. These film-forming materials still have many shortcomings in practical applications: Firstly, traditional film-forming systems have a simple molecular network structure, poor film flexibility, and low tensile strength. During storage and transportation, they are easily subjected to compression, friction, and temperature and humidity fluctuations, leading to problems such as brittleness, film breakage, and fragrance leakage, severely affecting the structural stability of the fragrance beads. Secondly, conventional water-soluble films lack antibacterial capabilities. When fragrance beads are stored in a humid environment for a long time, bacteria, mold, and other microorganisms easily adhere to and grow on the film surface, causing the product to mold, deteriorate, and develop odors, shortening the product's shelf life.
[0004] Therefore, this application is submitted. Summary of the Invention
[0005] This invention provides a laundry fragrance bead and its preparation method. The water-soluble film described in this application has excellent mechanical properties and antibacterial properties, thereby improving the stability and antibacterial properties of the laundry fragrance bead.
[0006] The present invention solves its technical problem by adopting the following technical solution: A laundry fragrance bead includes a water-soluble membrane and contents encapsulated within the water-soluble membrane. The water-soluble membrane comprises the following raw materials in weight percentage: 2-3% polysaccharide material, 2-5% adsorbent, 5-8% quaternary ammonium salt material, 5-8% polyol, 0.5-2% oleamide, 0.2-0.8% calcium oxide, and the balance being a modified starch aqueous solution. The quaternary ammonium salt material is hydroxypropyltrimethylammonium chloride chitosan.
[0007] As an embodiment of this application, the polysaccharide material is trehalose.
[0008] As an embodiment of this application, the polyol is at least one selected from glycerol, ethylene glycol, propylene glycol, butylene glycol, pentanediol, hexanediol, glycerol, neopentanediol, pentaerythritol, and sorbitol.
[0009] As an embodiment of this application, the adsorbent is at least one of calcium carbonate and zeolite powder.
[0010] As an embodiment of this application, the modified starch in the modified starch aqueous solution has a mass percentage content of 28-35%.
[0011] As an embodiment of this application, the method for preparing the modified starch is as follows: (1) Add corn starch, isoamylase, pullulanase to water, adjust the pH to 5.8-6.5, and perform enzymatic hydrolysis to obtain the hydrolysate; (2) Add hydrolyzed chitosan to the enzymatic hydrolysate, then add epichlorohydrin, adjust the pH of the reaction to 8-9, react, centrifuge, dry, and obtain modified starch.
[0012] As an embodiment of this application, the mass ratio of corn starch, isoamylase, pullulanase, and water is 1:(0.004~0.008):(0.004~0.008):(2~10).
[0013] As an embodiment of this application, the mass ratio of the hydrolyzed chitosan, enzymatic hydrolysate, and epichlorohydrin is (0.2~0.3):(2~10):(0.05~0.08).
[0014] As an embodiment of this application, the enzymatic hydrolysis temperature is 44~50℃ and the enzymatic hydrolysis time is 1~10h; The reaction is carried out at a temperature of 45-60°C for 2-6 hours.
[0015] As an embodiment of this application, the method for preparing the water-soluble membrane is as follows: a modified starch aqueous solution, polysaccharide material, adsorbent, polyol, oleic acid amide and calcium oxide are mixed evenly, gelatinized, degassed, and cast into a film to obtain a water-soluble membrane.
[0016] The beneficial effects of this invention are as follows: This application uses polysaccharide materials, adsorbents, quaternary ammonium salt materials, polyols, oleamide, calcium oxide, and modified starch as raw materials for preparing water-soluble films. Modified starch and polysaccharide materials are used as composite film-forming matrices, supplemented by adsorbents, quaternary ammonium salt materials, polyols, oleamide, and calcium oxide to prepare multifunctional water-soluble films. Through hydrogen bonding, physical filling, and composite antibacterial effects, the components construct a stable three-dimensional network film-forming structure, which effectively improves the mechanical properties and antibacterial properties of the water-soluble film, thereby improving the stability and antibacterial properties of laundry fragrance beads. Detailed Implementation
[0017] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0018] In this invention, the technical features described in an open-ended manner include both closed-ended technical solutions composed of the listed features and open-ended technical solutions that include the listed features.
[0019] In this invention, numerical ranges are involved. Unless otherwise specified, the numerical ranges are considered continuous and include the minimum and maximum values of the range, as well as every value between the minimum and maximum values. Furthermore, when the range refers to integers, it includes every integer between the minimum and maximum values of the range. Additionally, when multiple ranges are provided to describe features or characteristics, the ranges may be merged. In other words, unless otherwise specified, all ranges disclosed herein should be understood to include any and all subranges to which they are included.
[0020] In this invention, there are no particular limitations on the specific dispersion and stirring methods.
[0021] Unless otherwise specified, all reagents or instruments used in this invention are commercially available conventional products. Unless otherwise specified, the raw materials used in each comparative example and the parallel experiments of each embodiment are the same commercially available products.
[0022] Hydroxypropyltrimethylammonium chloride chitosan: Guangzhou Mingcheng Biotechnology.
[0023] Zeolite powder: Lingshou County Qiangdong Mineral Products Processing Plant, 600 mesh.
[0024] Pullulanase (FDY-2224), α-amylase (GDG-2011), and β-amylase (FDG-2258) were all derived from Xiasheng (Beijing) Biotechnology.
[0025] The isoamylase was obtained from Hubei Weishi Chemical Reagent, with an enzyme activity of 10000u / g.
[0026] Corn starch: Yufeng Industrial Group.
[0027] Fatty alcohol polyoxyethylene ether: AEO-9, Wanhua Chemical.
[0028] This application provides a laundry fragrance bead, comprising a water-soluble membrane and contents encapsulated within the water-soluble membrane. The water-soluble membrane comprises the following raw materials by mass percentage: 2-3% polysaccharide material, 2-5% adsorbent, 5-8% quaternary ammonium salt material, 5-8% polyol, 0.5-2% oleamide, 0.2-0.8% calcium oxide, and the balance being a modified starch aqueous solution. The quaternary ammonium salt material is hydroxypropyltrimethylammonium chloride chitosan.
[0029] This application uses polysaccharide materials, adsorbents, quaternary ammonium salt materials, polyols, oleamide, calcium oxide, and modified starch as raw materials for preparing water-soluble membranes. Modified starch and polysaccharide materials are used as composite film-forming matrices, supplemented by adsorbents, quaternary ammonium salt materials, polyols, oleamide, and calcium oxide to prepare multifunctional water-soluble membranes. Through hydrogen bonding, physical filling, and composite antibacterial effects, the components construct a stable three-dimensional network film-forming structure, effectively improving the mechanical properties and antibacterial properties of the water-soluble membrane, thereby enhancing the stability and antibacterial properties of laundry fragrance beads.
[0030] The modified starch and polysaccharide materials serve as the main composite film-forming matrix, generating numerous intermolecular hydrogen bonds with the polysaccharide materials to jointly construct a continuous and complete film-forming framework. This improves the brittleness and cracking defects of single starch films, endowing the film with mechanical strength and antibacterial properties. Polyols, as small-molecule plasticizers, weaken the intermolecular forces, enhance molecular chain fluidity, and significantly improve film flexibility. Oleamide eliminates internal stress during film formation, reduces microscopic defects such as pinholes and microcracks, and improves film surface lubrication. Simultaneously, the adsorbent and calcium oxide act as physical fillers and structural reinforcements, filling the internal pores of the film network and further improving the density and mechanical properties of the water-soluble film.
[0031] In some embodiments, the polysaccharide material is trehalose.
[0032] In some embodiments, the polyol is at least one selected from glycerol, ethylene glycol, propylene glycol, butylene glycol, pentanediol, hexanediol, glycerol, neopentanediol, pentaerythritol, and sorbitol.
[0033] In some embodiments, the adsorbent is at least one of calcium carbonate and zeolite powder.
[0034] In some embodiments, the particle size of the adsorbent is 100-1000 mesh.
[0035] In some embodiments, the modified starch in the modified starch aqueous solution has a mass percentage content of 28-35%.
[0036] In some embodiments, the modified starch is prepared by: (1) Add corn starch, isoamylase, pullulanase to water, adjust the pH to 5.8-6.5, and perform enzymatic hydrolysis to obtain the hydrolysate; (2) Add hydrolyzed chitosan to the enzymatic hydrolysate, then add epichlorohydrin, adjust the pH of the reaction to 8-9, react, centrifuge, dry, and obtain modified starch.
[0037] This application utilizes isoamylase and pullulanase to hydrolyze corn starch, effectively improving its structure and optimizing the branched and linear chains. Subsequently, hydrolyzed chitosan is used for functional modification. The modified starch can form numerous intermolecular hydrogen bonds with polysaccharides and hydroxypropyltrimethylammonium chloride chitosan, collectively constructing a continuous and complete film-forming framework, forming a dense three-dimensional network structure. This effectively blocks microorganisms and adsorbs negatively charged microbial cell membranes, disrupting cell structure and inhibiting metabolism, thus achieving bactericidal and bacteriostatic effects. This effectively improves the mechanical and antibacterial properties of the water-soluble film, thereby enhancing the stability and antibacterial properties of laundry fragrance beads.
[0038] In some embodiments, the mass ratio of corn starch, isoamylase, pullulanase, and water is 1:(0.004~0.008):(0.004~0.008):(2~10).
[0039] In some embodiments, the mass ratio of the hydrolyzed chitosan, enzymatic hydrolysate, and epichlorohydrin is (0.2~0.3):(2~10):(0.05~0.08).
[0040] In some embodiments, the enzymatic hydrolysis temperature is 44~50℃ and the enzymatic hydrolysis time is 1~10h.
[0041] In some embodiments, the reaction is carried out at a temperature of 45-60°C for 2-6 hours.
[0042] In some embodiments, the water-soluble film is prepared by mixing modified starch aqueous solution, polysaccharide material, adsorbent, polyol, oleic acid amide and calcium oxide evenly, gelatinizing, degassing, and casting into a film to obtain a water-soluble film.
[0043] In some embodiments, the contents comprise the following components by weight percentage: 2-5% hydrogenated castor oil, 10-20% propylene glycol, 8-15% glycerin, 2-8% cocamidopropyl betaine, 25-35% fatty alcohol polyoxyethylene ether (AEO-9), 0.5-2% microencapsulated flavoring, 5-8% silica, and the balance being water.
[0044] The present application is further illustrated below with specific embodiments:
[0045] Example 1 A method for preparing a water-soluble film includes the following steps: (1) Preparation of modified starch: Corn starch, isoamylase and pullulanase were added to water, the pH was adjusted to 6.2, and the mixture was enzymatically hydrolyzed at 48°C for 2 hours. The mixture was then cooled to room temperature to obtain the enzymatic hydrolysate. Hydrolyzed chitosan was added to the enzymatic hydrolysate, and epichlorohydrin was added. The pH of the reaction was adjusted to 8.5, and the mixture was reacted at 55°C for 4.5 hours. The mixture was then centrifuged and dried to obtain the modified starch.
[0046] The mass ratio of corn starch, isoamylase, pullulanase, and water is 1:0.005:0.006:4; the mass ratio of hydrolyzed chitosan, enzymatic hydrolysate, and epichlorohydrin is 0.25:5:0.06.
[0047] (2) Weigh the following raw materials according to the mass percentage ratio: 2.5% trehalose, 3% zeolite powder, 6% hydroxypropyltrimethylammonium chloride chitosan, 7% glycerol, 1.2% oleamide, 0.6% calcium oxide, and the balance being a modified starch aqueous solution. The modified starch aqueous solution contains 30% modified starch by mass.
[0048] (3) Mix the modified starch aqueous solution, trehalose, zeolite powder, hydroxypropyltrimethylammonium chloride chitosan, glycerol, oleamide and calcium oxide evenly, gelatinize at 115℃ for 15 min, then put it into a vacuum box with a vacuum degree of 0.1 Pa to degas for 20 min, cast it into a film in a mold, and finally dry it at 50℃ for 12 h to obtain a water-soluble film.
[0049] Example 2 A method for preparing a water-soluble film includes the following steps: (1) Preparation of modified starch: Corn starch, isoamylase and pullulanase were added to water, the pH was adjusted to 6.2, and the mixture was enzymatically hydrolyzed at 48°C for 2 hours. The mixture was then cooled to room temperature to obtain the enzymatic hydrolysate. Hydrolyzed chitosan was added to the enzymatic hydrolysate, and epichlorohydrin was added. The pH of the reaction was adjusted to 8.5, and the mixture was reacted at 55°C for 4.5 hours. The mixture was then centrifuged and dried to obtain the modified starch.
[0050] The mass ratio of corn starch, isoamylase, pullulanase, and water is 1:0.004:0.008:4; the mass ratio of hydrolyzed chitosan, enzymatic hydrolysate, and epichlorohydrin is 0.2:5:0.08.
[0051] (2) Weigh the following raw materials according to the mass percentage ratio: 2% trehalose, 5% zeolite powder, 5% hydroxypropyltrimethylammonium chloride chitosan, 8% glycerol, 0.5% oleamide, 0.8% calcium oxide, and the balance being a modified starch aqueous solution. The modified starch aqueous solution contains 30% modified starch by mass.
[0052] (3) Mix the modified starch aqueous solution, trehalose, zeolite powder, hydroxypropyltrimethylammonium chloride chitosan, glycerol, oleamide and calcium oxide evenly, gelatinize at 115℃ for 15 min, then put it into a vacuum box with a vacuum degree of 0.1 Pa to degas for 20 min, cast it into a film in a mold, and finally dry it at 50℃ for 12 h to obtain a water-soluble film.
[0053] Example 3 A method for preparing a water-soluble film includes the following steps: (1) Preparation of modified starch: Corn starch, isoamylase and pullulanase were added to water, the pH was adjusted to 6.2, and the mixture was enzymatically hydrolyzed at 48°C for 2 hours. The mixture was then cooled to room temperature to obtain the enzymatic hydrolysate. Hydrolyzed chitosan was added to the enzymatic hydrolysate, and epichlorohydrin was added. The pH of the reaction was adjusted to 8.5, and the mixture was reacted at 55°C for 4.5 hours. The mixture was then centrifuged and dried to obtain the modified starch.
[0054] The mass ratio of corn starch, isoamylase, pullulanase, and water is 1:0.008:0.004:4; the mass ratio of hydrolyzed chitosan, enzymatic hydrolysate, and epichlorohydrin is 0.3:5:0.05.
[0055] (2) Weigh the following raw materials according to the mass percentage ratio: 3% trehalose, 2% zeolite powder, 8% hydroxypropyltrimethylammonium chloride chitosan, 5% glycerol, 2% oleamide, 0.2% calcium oxide, and the balance being a modified starch aqueous solution. The modified starch aqueous solution contains 30% modified starch by mass.
[0056] (3) Mix the modified starch aqueous solution, trehalose, zeolite powder, hydroxypropyltrimethylammonium chloride chitosan, glycerol, oleamide and calcium oxide evenly, gelatinize at 115℃ for 15 min, then put it into a vacuum box with a vacuum degree of 0.1 Pa to degas for 20 min, cast it into a film in a mold, and finally dry it at 50℃ for 12 h to obtain a water-soluble film.
[0057] Example 4 A method for preparing laundry fragrance beads includes the following steps: (1) Preparation of contents Weigh the following raw materials according to the following weight percentages: 3.5% hydrogenated castor oil, 15% propylene glycol, 12% glycerin, 5% cocamidopropyl betaine, 30% fatty alcohol polyoxyethylene ether (AEO-9), 1.5% microencapsulated flavoring, 6% silica, and the balance being water.
[0058] Hydrogenated castor oil, propylene glycol, and glycerin were mixed evenly, then microcapsule flavoring was added and mixed evenly, followed by cocamidopropyl betaine and fatty alcohol polyoxyethylene ether (AEO-9), and finally the remaining materials were added and mixed evenly. The mixture was then placed in a vacuum chamber with a vacuum degree of 0.1 Pa for 20 minutes to degas and obtain the contents.
[0059] (2) The contents are wrapped with a water-soluble film to obtain laundry fragrance beads.
[0060] Comparative Example 1 The difference between Comparative Example 1 and Example 1 is that an equal amount of corn starch was used to replace the modified starch, while everything else was the same.
[0061] A method for preparing a water-soluble film includes the following steps: (1) Weigh the following raw materials according to the mass percentage ratio: 2.5% trehalose, 3% zeolite powder, 6% hydroxypropyltrimethylammonium chloride chitosan, 7% glycerol, 1.2% oleamide, 0.6% calcium oxide, and the balance being an aqueous solution of corn starch. The corn starch aqueous solution contains 30% corn starch by mass.
[0062] (3) Mix corn starch aqueous solution, trehalose, zeolite powder, hydroxypropyltrimethylammonium chloride chitosan, glycerol, oleamide and calcium oxide evenly, gelatinize at 115℃ for 15min, then put it into a vacuum box with a vacuum degree of 0.1Pa for 20min to degas, cast it into a film in a mold, and finally dry it at 50℃ for 12h to obtain a water-soluble film.
[0063] Comparative Example 2 The difference between Comparative Example 2 and Example 1 is that an equal amount of modified starch was used to replace hydroxypropyltrimethylammonium chloride chitosan, and the mass percentage of modified starch in the modified starch aqueous solution was increased to 35%, while all other aspects remained the same.
[0064] A method for preparing a water-soluble film includes the following steps: (1) Preparation of modified starch: Corn starch, isoamylase and pullulanase were added to water, the pH was adjusted to 6.2, and the mixture was enzymatically hydrolyzed at 48°C for 2 hours. The mixture was then cooled to room temperature to obtain the enzymatic hydrolysate. Hydrolyzed chitosan was added to the enzymatic hydrolysate, and epichlorohydrin was added. The pH of the reaction was adjusted to 8.5, and the mixture was reacted at 55°C for 4.5 hours. The mixture was then centrifuged and dried to obtain the modified starch.
[0065] The mass ratio of corn starch, isoamylase, pullulanase, and water is 1:0.005:0.006:4; the mass ratio of hydrolyzed chitosan, enzymatic hydrolysate, and epichlorohydrin is 0.25:5:0.06.
[0066] (2) Weigh the following raw materials according to the mass percentage ratio: 2.5% trehalose, 3% zeolite powder, 6% hydroxypropyltrimethylammonium chloride chitosan, 7% glycerol, 1.2% oleamide, 0.6% calcium oxide, and the balance being a modified starch aqueous solution. The modified starch aqueous solution contains 35.0% modified starch by mass.
[0067] (3) Mix the modified starch aqueous solution, trehalose, zeolite powder, hydroxypropyltrimethylammonium chloride chitosan, glycerol, oleamide and calcium oxide evenly, gelatinize at 115℃ for 15 min, then put it into a vacuum box with a vacuum degree of 0.1 Pa to degas for 20 min, cast it into a film in a mold, and finally dry it at 50℃ for 12 h to obtain a water-soluble film.
[0068] Comparative Example 3 The difference between Comparative Example 3 and Example 1 is that the preparation method of corn starch is different from that of Example 1, but everything else is the same.
[0069] A method for preparing a water-soluble film includes the following steps: (1) Preparation of modified starch: Corn starch, α-amylase and β-amylase were added to water, the pH was adjusted to 6.2, and the mixture was enzymatically hydrolyzed at 48℃ for 2 h. The mixture was then cooled to room temperature to obtain the enzymatic hydrolysate. Hydrolyzed chitosan was added to the enzymatic hydrolysate, and epichlorohydrin was added. The pH of the reaction was adjusted to 8.5, and the mixture was reacted at 55℃ for 4.5 h. The mixture was then centrifuged and dried to obtain the modified starch.
[0070] The mass ratio of corn starch, α-amylase, β-amylase, and water is 1:0.005:0.006:4; the mass ratio of hydrolyzed chitosan, enzymatic hydrolysate, and epichlorohydrin is 0.25:5:0.06.
[0071] (2) Weigh the following raw materials according to the mass percentage ratio: 2.5% trehalose, 3% zeolite powder, 6% hydroxypropyltrimethylammonium chloride chitosan, 7% glycerol, 1.2% oleamide, 0.6% calcium oxide, and the balance being a modified starch aqueous solution. The modified starch aqueous solution contains 30% modified starch by mass.
[0072] (3) Mix the modified starch aqueous solution, trehalose, zeolite powder, hydroxypropyltrimethylammonium chloride chitosan, glycerol, oleamide and calcium oxide evenly, gelatinize at 115℃ for 15 min, then put it into a vacuum box with a vacuum degree of 0.1 Pa to degas for 20 min, cast it into a film in a mold, and finally dry it at 50℃ for 12 h to obtain a water-soluble film.
[0073] Comparative Example 4 The difference between Comparative Example 4 and Example 1 is that the preparation method of corn starch is different from that of Example 1, but everything else is the same.
[0074] A method for preparing a water-soluble film includes the following steps: (1) Preparation of modified starch: Corn starch, isoamylase and pullulanase were added to water, the pH was adjusted to 6.2, enzymatic hydrolysis was carried out at 48℃ for 2 hours, cooled to room temperature, centrifuged and dried to obtain modified starch.
[0075] The mass ratio of corn starch, isoamylase, pullulanase, and water is 1:0.005:0.006:4.
[0076] (2) Weigh the following raw materials according to the mass percentage ratio: 2.5% trehalose, 3% zeolite powder, 6% hydroxypropyltrimethylammonium chloride chitosan, 7% glycerol, 1.2% oleamide, 0.6% calcium oxide, and the balance being a modified starch aqueous solution. The modified starch aqueous solution contains 30% modified starch by mass.
[0077] (3) Mix the modified starch aqueous solution, trehalose, zeolite powder, hydroxypropyltrimethylammonium chloride chitosan, glycerol, oleamide and calcium oxide evenly, gelatinize at 115℃ for 15 min, then put it into a vacuum box with a vacuum degree of 0.1 Pa to degas for 20 min, cast it into a film in a mold, and finally dry it at 50℃ for 12 h to obtain a water-soluble film.
[0078] Test case 1. The tensile strength was tested using an electronic universal testing machine.
[0079] 2. Antibacterial properties: Staphylococcus aureus and Escherichia coli were used as test strains. 250 μL of bacterial suspension (concentration 10) was taken. 6 Add CFU / mL to 25mL of broth medium, shake the mixture well, and pour it onto the top layer of a 1.8% agar plate. After solidification, place a water-soluble film cut into round pieces (8mm in diameter) on the plate and incubate for 18 hours. Observe the diameter of the inhibition zone, measure and record it using a vernier caliper.
[0080] Table 1
[0081] As can be seen from Table 1, the water-soluble membrane described in this application has excellent mechanical properties and antibacterial properties.
[0082] Comparing Example 1 with Comparative Examples 1-2, it can be seen that the modified starch prepared in this application and the hydroxypropyltrimethylammonium chloride chitosan have a significant synergistic effect in antibacterial properties. The synergistic effect of the two not only improves the antibacterial properties, but also significantly improves the mechanical properties. The lack of hydroxypropyltrimethylammonium chloride chitosan or the use of corn starch to replace the modified starch will lead to a significant decrease in both antibacterial and mechanical properties.
[0083] Comparing Example 1 with Comparative Examples 3-4, it can be seen that the modified starch prepared using this application can significantly improve antibacterial properties and mechanical properties.
[0084] 3. Prepare laundry fragrance beads from the water-soluble films of Examples 1-3 and Comparative Examples 1-4 according to the method of Example 4. Place the laundry fragrance beads at 25°C and 50°C for 1 month respectively and observe for any abnormalities.
[0085] Table 2
[0086] As can be seen from Table 2, the laundry fragrance beads prepared by the water-soluble film described in this application have excellent stability.
[0087] Comparing Example 1 with Comparative Examples 1-2, it can be seen that the modified starch prepared in this application and the hydroxypropyltrimethylammonium chloride chitosan can synergistically improve stability. The lack of hydroxypropyltrimethylammonium chloride chitosan or the use of corn starch to replace the modified starch will lead to a significant decrease in stability.
[0088] Comparing Example 1 with Comparative Examples 3-4, it can be seen that the modified starch prepared using this application can significantly improve stability.
[0089] 4. The water-soluble film from Example 1 was prepared into laundry fragrance beads according to the method in Example 4, and tested according to the provisions of GB / T13174-2008. During the test, 300 mg / kg water was used, the sample concentration was 0.2%, the temperature was kept constant at 30℃ and the rotation speed was kept constant at 120 r / min for 20 minutes, then stopped. After rinsing twice and drying, the whiteness value before and after washing was measured.
[0090] Table 3
[0091] As can be seen from Table 3, the laundry fragrance beads described in this application have a good stain removal effect.
[0092] Finally, it should be noted that the above embodiments are used to illustrate the technical solutions of the present invention and not to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to preferred embodiments, those skilled in the art should understand that modifications or equivalent substitutions can be made to the technical solutions of the present invention without departing from the essence and scope of the technical solutions of the present invention.
Claims
1. A laundry fragrance bead, characterized in that, The product includes a water-soluble membrane and contents encapsulated within the water-soluble membrane. The water-soluble membrane comprises the following raw materials in weight percentage: 2-3% polysaccharide material, 2-5% adsorbent, 5-8% quaternary ammonium salt material, 5-8% polyol, 0.5-2% oleamide, 0.2-0.8% calcium oxide, and the balance being a modified starch aqueous solution. The quaternary ammonium salt material is hydroxypropyltrimethylammonium chloride chitosan.
2. The laundry fragrance beads according to claim 1, characterized in that, The polysaccharide material is trehalose.
3. The laundry fragrance beads according to claim 1, characterized in that, The polyol is at least one selected from glycerol, ethylene glycol, propylene glycol, butylene glycol, pentanediol, hexanediol, glycerol, neopentanediol, pentaerythritol, and sorbitol.
4. The laundry fragrance beads according to claim 1, characterized in that, The adsorbent is at least one of calcium carbonate and zeolite powder.
5. The laundry fragrance beads according to claim 1, characterized in that, The modified starch aqueous solution contains 28-35% modified starch by mass.
6. The laundry fragrance beads according to claim 1, characterized in that, The modified starch is prepared by: (1) Add corn starch, isoamylase, pullulanase to water, adjust the pH to 5.8-6.5, and perform enzymatic hydrolysis to obtain the hydrolysate; (2) Add hydrolyzed chitosan to the enzymatic hydrolysate, then add epichlorohydrin, adjust the pH of the reaction to 8-9, react, centrifuge, dry, and obtain modified starch.
7. The laundry fragrance beads according to claim 6, characterized in that, The mass ratio of corn starch, isoamylase, pullulanase, and water is 1:(0.004~0.008):(0.004~0.008):(2~10).
8. The laundry fragrance beads according to claim 6, characterized in that, The mass ratio of the hydrolyzed chitosan, enzymatic hydrolysate, and epichlorohydrin is (0.2~0.3):(2~10):(0.05~0.08).
9. The laundry fragrance beads according to claim 6, characterized in that, The enzymatic hydrolysis temperature is 44~50℃, and the enzymatic hydrolysis time is 1~10h; The reaction is carried out at a temperature of 45-60°C for 2-6 hours.
10. The laundry fragrance beads according to any one of claims 1 to 9, characterized in that, The method for preparing the water-soluble film is as follows: a modified starch aqueous solution, polysaccharide material, adsorbent, polyol, oleic acid amide and calcium oxide are mixed evenly, gelatinized, degassed and cast into a film to obtain a water-soluble film.